2010
DOI: 10.1002/ejoc.201000221
|View full text |Cite
|
Sign up to set email alerts
|

1,4,7,10‐Tetraisoalkyltetracenes: Tuning of Solid‐State Optical Properties and Fluorescence Quantum Yields by Peripheral Modulation

Abstract: We have synthesized 1,4,7,10-tetraisoalkyltetracenes from a 2,6-naphthodiyne precursor and 2,5-diisoalkylfurans as the starting materials (isoalkyl: isopropyl, isobutyl, and isopentyl). The tetracene molecules exhibited crystallochromy: The solid-state colors of the isopropyl, isobutyl, and isopentyl derivatives were yellow, red, and orange-yellow, respectively. In contrast, there were no marked differences in the optical properties of these compounds in solution. The isopropyl derivative exhibited the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…56 Similarly, Barrett and co-workers reported that the cycloaddition of 1,4-difluoro-2,5-dimethoxybenzene 5 as a 70 dienophile precursor with furan derivatives 6 afforded a series of functionalized anthracenes 11 and 12. In this example, 1,4difluoro-2,5-dimethoxybenzene 5 was used as iterative double benzyne as shown in Scheme 3.…”
Section: Diels-alder Reaction With Dienesmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Similarly, Barrett and co-workers reported that the cycloaddition of 1,4-difluoro-2,5-dimethoxybenzene 5 as a 70 dienophile precursor with furan derivatives 6 afforded a series of functionalized anthracenes 11 and 12. In this example, 1,4difluoro-2,5-dimethoxybenzene 5 was used as iterative double benzyne as shown in Scheme 3.…”
Section: Diels-alder Reaction With Dienesmentioning
confidence: 99%
“…As shown in 15 Scheme 4, the bis(aryne) precursor compound 13 was subjected to a Diels-Alder reaction with 2,5-dialkylfurans 14 followed by deoxygenation of the adduct 15 in the presence of hydrogen and Pd/C to afford 1,4,7,10-tetraalkyl tetracene 16. [68][69][70][71] In addition, unsubstituted pentacene can also be synthesized by using an 20 aryne as the starting material. Müllen's group reported the use of pentacene and nonacene precursors.…”
Section: Diels-alder Reaction With Dienesmentioning
confidence: 99%
“…For the synthesis, see: Kitamura et al (2011). For structures of related alkylsubstituted tetracene derivatives, see: Kitamura, Abe et al (2010); Kitamura, Tsukuda et al (2010).…”
Section: Related Literaturementioning
confidence: 99%
“…addition, we have recently found that alkyl-substituted tetracenes possess interesting chromophore properties. Depending on the length, shape, and the number of alkyl side chains, the solid-state color of the tetetracenes varies through yellow, orange and red (Kitamura, Abe et al, 2010;Kitamura, Tsukuda et al, 2010). The difference in color can be attributed to crystallochromy (Klebe, et al, 1989), i.e.…”
Section: Data Collectionmentioning
confidence: 99%
“…For the preparation and solid-state fluorescence studies of 1,4,5,8-tetraalkylanthracenes, see: Kitamura et al (2007). For a related structure, see: Kitamura et al (2010). For related herringbone structures, see: Curtis et al (2004).…”
Section: Related Literaturementioning
confidence: 99%